LENGTH-WEIGHT RELATIONSHIP OF INDIAN MOTTLED EEL, ANGUILLA BENGALENSIS (GRAY, 1831) FROM THE RIVER GODAVARI AND THE RIVER KRISHNA BASIN, INDIA - GHATGE, SWAPNIL; PATIL, KRISHNA; SHETKAR, MAHESH; GANGAN, SHARDUL; KHARATMOL, BALAJI (Journal of the Inland Fisheries Society of India, 2024)
Anguilla bengalensis is found in India (Kerala, Andhra Pradesh, Arunachal Pradesh, Manipur, Meghalaya, Orissa, Tamil Nadu, Assam, and Nagaland), Pakistan, Bangladesh, Nepal (Gandaki, Koshi, Karnali, Mahakali), Sri Lanka, Myanmar, South Africa (Jayaram, 1999; Pike   et al., 2020). This species inhabits various niches in river systems from quiet undisturbed areas containing mud substrate to deep water, fast-flowing rock pools of rivers (Bell-Cross and Minshull 1988). A bony fish belonging to the order Anguilliformes of the family Anguillidae, A. bengalensis is a commercially important food and in addition, A. bengalensis is considered a 'pristine rare ornamental species of the Himalayan drainage often being preserved in temple ponds for religious purposes (Shrestha, 2003). It is a catadromous, semelparous species with multiple life stages (Tesch, 2003; Jacoby et al., 2015). The species is subject to heavy fishing pressure, leading to an alarming decline in natural populations. In support of its conservation this species has been declared as 'Near Threatened' according to IUCN criteria (Molur and Walker 1998, Pike et al., 2020).